Segmented analysis of official statistical indicators dynamic series for osteoarthritis in 1994–2018 in Russia, the North-Western Federal district and the Arkhangelsk region - M. V. Makarova; M. Yu. Valkov (Научно-практическая ревматология, 2021)
To improve the rheumatology service in the Russian Federation, it is necessary to determine the true extent of primary and general incidence of osteoarthritis (OA).The aim of the study is a detailed assessment of trends in the dynamics of OA incidence in the Russian Federation, the North-Western Federal district (NWFD) and the Arkhangelsk region (AR).Materials and methods. We evaluated trends in the dynamics of both incidence and prevalence of OA in the Russian Federation (RF), NWFD and AR in the period 1994–2018 based on data from the annual statistical reports of the Ministry of health of the Russian Federation (form 12). Data on the population of AR were obtained in the regional Bureau of statistics – Archangelskstat, for the northwestern Federal district and the Russian Federation from freely available statistical collections of Rosstat. We analyzed the indicators of the adult population (over 18 years old). To evaluate time trends, we used segmented analysis using the Joinpoint Regression Program (National Cancer Institute, USA) to analyze linear trends, evaluate their statistical significance, and identify time points of their change (joinpoints).Results. In the period from 2004 to 2012 in Russia was a decline in the number of annually detected cases of OA, the prevalence of OA increased steadily in the 2016 year recorded a decline in the number of cases of OA in NWFD and AR. The analysis showed a discrepancy in the trends of incidence of OA in the Russian Federation, the northwestern Federal district and AR, which was nonlinear and chaotic. In all territories, the prevalence was increasing. In the Russian Federation, the period from 2004 to 2008, when the primary incidence of OA fell sharply, was marked by a stable increase in the prevalence from 2041.6 to 3383.3 per 100 thousand population. Conclusion. Analysis of official statistical information on the both incidence and prevalence of OA shows a significant variation in indicators, their fluctuations are not related to changes in the practice of diagnosis and treatment of this disease and, most likely, are associated with gaps in its accounting. Improving the epidemiological assessment of OA is possible with the introduction of a system of personalized patient registration-the osteoarthritis registry.